Extended hildebrand solubility approach applied to nimodipine in peg 400 + ethanol mixtures (2013)
Nimodipine (NMD) is a drug used as cerebral vasodilator whose physicochemical properties in solution have not been studied completely. In this work the Extended Hildebrand Solubility Approach (EHSA) was applied to evaluate the equilibrium solubility of NMD in some polyethylene glycol 400 + ethanol mixtures at 298.15 K. An acceptable correlative capacity of EHSA was found using a regular polynomial model in order three (overall deviation lower than 1.3%), when the W interaction parameter is related to the solubility parameter of the mixtures. Moreover, the mean deviation obtained in the estimated solubility with respect to experimental solubility was lower than the one obtained directly by means of an empiric regression in order three of the logarithm experimental solubility as a function of the mixtures' solubility parameters (1.7%).